Home networks for independent living, support and care services: Issues impinging on the successful introduction of products and services - Martyn Cooper (1998)
Home Networks ("Smart Houses") will potentially enable disabled and elderly people to live independently and support various services delivered to their homes. Although this has been demonstrated in a number of projects, this paper outlines key challenges to be met if this potential is to be realised widely.